Analisis Determinan Keberhasilan Program Gerakan Pembangunan Desa Terpadu (Gerbang Sadu) Mandara di Kecamatan Karangasem - Dewi, Ni Luh Yuliani; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.10.TAHUN 2018DO - 10.24843/EEB.2018.v07.i10.p03, 2018)
The problems facing nations that need the right process of handling are poverty. As part of development, poverty alleviation requires a common perception of stakeholders that they require alignment in their implementation in order to achieve targeted, effective, efficient and sustainable results. In poverty alleviation programs, strategies are applied using the principle that if poor people have an opportunity to make independent decisions, they will be able to do much for themselves, their families and communities. Efforts that have been made by the Provincial Government of Bali in improving welfare and poverty alleviation through several strategies and policies. The Provincial Government of Bali has launched the Integrated Village Development Movement Program Mandara / Gerbang Sadu Mandara (GSM) as a place for rural communities to jointly build themselves and their communities independently and participatively. The Gerbang Sadu Mandara Program covers the development of rural infrastructure and the development of productive economic enterprises in rural areas which is one of the main programs in accelerating poverty reduction in Bali Province. This study aims to analyze the direct and indirect influence between Empowerment variables, Village Leadership Leadership, Community Participation and Success of Integrated Village Development Movement Program Mandara in District Karangasem. And the influence of moderation of advisory variables on empowerment relationship and leadership of village head to community participation. This research uses descriptive analysis technique and structural equation with SEM alternative PLS. The results showed that Empowerment and Leadership of Village Head variable have positive and significant influence to Community Participation System with R-Square value of 0.795. In addition, Empowerment variables, Village Leadership, Community Participation also have a positive and significant impact on Program Success with R-Square value of 0.867.